2021
DOI: 10.3390/en14144190
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Premixed Syngas/Air Combustion in Micro-channels: Impacts of Flow Rate and Fuel Composition

Abstract: Due to increasing demand for clean and green energy, a need exists for fuels with low emissions, such as synthetic gas (syngas), which exhibits excellent combustion properties and has demonstrated promise in low-emission energy production, especially at microscales. However, due to complicated flame properties in microscale systems, it is of utmost importance to describe syngas combustion and comprehend its properties with respect to its boundary and inlet conditions, and its geometric characteristics. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…In the event of FREI, the flame could not sustain itself due to unrestrained heat loss through the microreactor wall; however, after the flame extinguished, the supply of the fresh fuel-air mixture eventually reached the high-temperature zone downstream of the channel and ignited again. Such phenomenon is detected numerically and experimentally in the literature [27][28][29]34]. To better comprehend the FREI phenomena, a specific case with an inlet velocity of 0.2 m/s is presented in this section.…”
Section: Stable Flame Metrics: Location and Spanmentioning
confidence: 92%
See 2 more Smart Citations
“…In the event of FREI, the flame could not sustain itself due to unrestrained heat loss through the microreactor wall; however, after the flame extinguished, the supply of the fresh fuel-air mixture eventually reached the high-temperature zone downstream of the channel and ignited again. Such phenomenon is detected numerically and experimentally in the literature [27][28][29]34]. To better comprehend the FREI phenomena, a specific case with an inlet velocity of 0.2 m/s is presented in this section.…”
Section: Stable Flame Metrics: Location and Spanmentioning
confidence: 92%
“…Preliminary trials in the setup of the model utilized herein showed that such a time step is sufficient in producing accurate simulation results that successfully predict the ignition characteristics. Additionally, this time step has been shown in the literature to be sufficiently small for capturing the microscale combustion phenomena, including the ones of interest in this study [27,34]. Furthermore, with the flame thickness being of the order of 1 mm, the chosen grid size ensured that the flame characteristics were resolved sufficiently within circa 15 cells.…”
Section: Operating Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas turbine can switch between fuel oil and fuel gas modes. While the fuel oil mode is primarily used during the initial ignition and later shutdown stages, the system transitions to the syngas combustion state once it achieves stability [30,31]. However, the complex composition of the syngas, along with the considerable variations in temperature and pressure, significantly impact the gas turbine's ability to maintain stable combustion operation.…”
Section: Process Condition Modelingmentioning
confidence: 99%
“…The transmission of heat, created during the combustion process, from the flame to the water steam introduced to the combustion chamber limits the participation of the thermal mechanism of nitric oxide creation, thus causing slight decrease in the NOx emission. Such a mechanism, in terms of low-temperature solid fuel boilers, has an insignificant effect on the amount of nitric oxides created during the combustion process because it is the fuel mechanism that has the greatest percentage of participation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%